Abs composite material for mobile phone holder and preparation method thereof

CN121873498BActive Publication Date: 2026-09-11ZHONGSHAN JIAQIN TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202512014174.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-12-29
Publication Date
2026-09-11
Estimated Expiration
2045-12-29

AI Technical Summary

Technical Problem

再者,手机支架常处于户外、车载等复杂环境中,要求材料具有优异的长期稳定性,包括抗紫外老化、抗热氧老化能力,以避免在使用过程中出现发黄、变脆、性能衰减等问题,而常规抗氧剂的添加难以在多相复合体系中实现长效、协同的稳定效果

Benefits of technology

本申请提供了一种用于手机支架的ABS复合材料,通过合理的配方设计与多组分功能协同,在不改变ABS树脂本体的前提下,构建了一个从分子界面到宏观尺度的复合增强稳定体系,从而同步且有效地提升了手机支架所需的刚性、韧性、耐磨抗滑性及长期稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121873498B_ABST
    Figure CN121873498B_ABST
Patent Text Reader

Abstract

The application provides an ABS composite material for a mobile phone support and a preparation method thereof, and belongs to the ABS composite material field.The ABS composite material is composed of the following raw materials: ABS resin: 100 parts, maleic anhydride grafted hydrogenated styrene-butadiene-styrene block copolymer: 8-15 parts, epoxy-polydimethylsiloxane oligomer: 2-5 parts, short carbon fiber: 5-10 parts, nano-silica / hyperbranched polyester / ABS master batch: 2-6 parts, phosphonate of N-alkyl-2,2,6,6-tetramethyl-4-aminopiperidine: 0.3-1.0 parts, and processing aid: 0.5-1.5 parts.Through reasonable formula design and multi-component function synergy, a composite reinforcing and stabilizing system from a molecular interface to a macro scale is constructed, so that the rigidity, toughness, wear resistance, slip resistance and long-term stability required by the mobile phone support are simultaneously and effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of ABS composite material technology, and in particular to an ABS composite material for mobile phone holders and its preparation method. Background Technology

[0002] ABS resin is widely used in the manufacture of electronic product casings and accessories, such as mobile phone stands, due to its excellent comprehensive mechanical properties, ease of processing, and cost advantages. However, as electronic products become increasingly sophisticated and thinner, and as users' requirements for user experience and durability continue to rise, traditional ABS materials or their simple modified products are gradually revealing performance limitations and contradictions when used in mobile phone stands.

[0003] Specifically, as a functional structural component, a phone holder first requires materials with sufficient rigidity (high strength, high modulus) to stably support the phone and resist deformation and creep under long-term load. Rigidity is usually improved by adding reinforcing phases such as glass fiber or carbon fiber, but this often leads to a decrease in material toughness and impact strength, making the holder prone to brittle fracture upon accidental drops or impacts, resulting in insufficient reliability. Conversely, if toughening is achieved by adding rubber elastomers, it inevitably sacrifices the material's rigidity, hardness, and heat resistance, falling into the traditional contradiction of "increasing rigidity leads to brittleness, increasing toughness leads to softness." Secondly, since the phone holder is in direct contact with the phone body, it needs excellent wear resistance and anti-slip properties to prevent repeated insertion and removal or friction scratches on the phone surface, while also providing sufficient friction to prevent the phone from slipping. Existing technologies often use secondary processing methods such as surface spraying and attaching silicone pads, which have problems such as easy coating wear and peeling, inconsistent feel, and increased processes and costs. Furthermore, mobile phone holders are often used in complex environments such as outdoors and in vehicles, requiring materials with excellent long-term stability, including resistance to UV aging and thermo-oxidative aging, to avoid problems such as yellowing, brittleness, and performance degradation during use. However, conventional antioxidants are difficult to achieve long-term, synergistic stability in multiphase composite systems. Therefore, the design and fabrication of an ABS composite material for mobile phone holders that can synergistically and integrally achieve high rigidity, high toughness, excellent surface wear resistance and anti-slip properties, and long-term dimensional and performance stability is crucial to meeting the stringent requirements of high-end mobile phone holders for comprehensive material performance. Summary of the Invention

[0004] This application provides an ABS composite material for mobile phone holders and a method for preparing the same, in order to solve the following technical problem: how to simultaneously improve the rigidity, toughness, wear resistance, anti-slip properties, and long-term stability of ABS composite materials for mobile phone holders.

[0005] In a first aspect, embodiments of this application provide an ABS composite material for a mobile phone holder, wherein the ABS composite material is composed of the following raw materials in parts by weight: ABS resin: 100 parts, maleic anhydride-grafted hydrogenated styrene-butadiene-styrene block copolymer: 8-15 parts, epoxy-polydimethylsiloxane oligomer: 2-5 parts, chopped carbon fiber: 5-10 parts, nano-silica / hyperbranched polyester / ABS masterbatch: 2-6 parts, N-alkyl-2,2,6,6-tetramethyl-4-aminopiperidine phosphonate: 0.3-1.0 parts, and processing aids: 0.5-1.5 parts.

[0006] Optionally, the preparation method of the maleic anhydride-grafted hydrogenated styrene-butadiene-styrene block copolymer includes the following steps: S101. Hydrogenated styrene-butadiene-styrene block copolymer, maleic anhydride monomer and dicumyl peroxide are stirred and mixed in a high-speed mixer at 60-80°C for 5-15 minutes to obtain a premix. S102. The premixed material is fed into a twin-screw extruder and subjected to a grafting reaction under melting temperature and shearing action. After water cooling and pelletizing, the maleic anhydride-grafted hydrogenated styrene-butadiene-styrene block copolymer is obtained. The mass ratio of the hydrogenated styrene-butadiene-styrene block copolymer, the maleic anhydride monomer, and the dicumyl peroxide is 100:(0.8-2.0):(0.1-0.4). The twin-screw extruder has a processing temperature of 170–190℃, a screw speed of 80–200 rpm, and a material residence time of 1–3 min. The grafting rate of the maleic anhydride-grafted hydrogenated styrene-butadiene-styrene block copolymer is 0.8-1.2%.

[0007] Optionally, the preparation method of the epoxy-polydimethylsiloxane oligomer includes the following steps: S201. Under vacuum conditions of 90-110℃, hydrogen-containing silicone oil and allyl glycidyl ether are dehydrated for 1-2 hours to obtain a mixture. S202. Under inert gas protection, the mixture is cooled to 80-90°C, then Karstedt catalyst is added, and the mixture is stirred at 80-90°C for 4-8 hours to obtain the epoxy-polydimethylsiloxane oligomer. The molar ratio of the silicon-hydrogen bonds in the hydrogen-containing silicone oil to the carbon-carbon double bonds in the allyl glycidyl ether is 1:(1.0-1.2). The mass of the Karstedt catalyst is 5 to 50 ppm of the mass of the hydrogen-containing silicone oil; The epoxy value of the epoxy-polydimethylsiloxane oligomer is 0.05 to 0.15.

[0008] Optionally, the preparation method of the nano-silica / hyperbranched polyester / ABS masterbatch includes the following steps: S301. Under nitrogen protection, trimethylolpropane, 2,2-dimethylolpropionic acid and p-toluenesulfonic acid catalyst are subjected to melt polycondensation reaction at 140-160°C for 6-10 hours to obtain hydroxyl-terminated hyperbranched polyester. S302. Mix nano-silica with the hyperbranched polyester at 80-100°C for 10-30 minutes to coat the surface of the nano-silica with the hyperbranched polyester, thereby obtaining a pretreated composite powder. S303. The pretreated composite powder and ABS resin are added to a twin-screw extruder for melt blending and extrusion granulation to obtain the nano-silica / hyperbranched polyester / ABS masterbatch. The twin-screw extruder has a processing temperature of 180–220°C and a screw speed of 200–400 rpm.

[0009] Optionally, the molar ratio of trimethylolpropane to 2,2-dimethylolpropionic acid is 1:(15-30); The mass of the p-toluenesulfonic acid catalyst is 1.0 to 3.0% of the mass of the 2,2-dimethylolpropionic acid. The mass ratio of the nano-silica to the hyperbranched polyester is 100:(5-20); The mass ratio of the pretreated composite powder to the ABS resin is (20-40):(60-80).

[0010] Optionally, the preparation method of the N-alkyl-2,2,6,6-tetramethyl-4-aminopiperidine phosphonate includes the following steps: S401. In the presence of potassium carbonate, (2,2,6,6-tetramethyl-piperidin-4-yl)-methylamine is reacted with iodoethane at 60-110 °C for 4-12 h to obtain an intermediate; S402. In the presence of the acid-binding agent triethylamine, the intermediate is subjected to a phosphonylation reaction with dimethylphosphonic chloride at room temperature for 1-3 hours to obtain a reaction solution containing the crude product. S403. The reaction solution is washed, separated, dried and concentrated, and then purified to obtain the N-alkyl-2,2,6,6-tetramethyl-4-aminopiperidine phosphonate.

[0011] Optionally, the molar ratio of (2,2,6,6-tetramethyl-piperidin-4-yl)-methylamine to iodoethane is 1:(1.0-1.5); The molar ratio of the intermediate to the dimethylphosphonic chloride is 1:(1.0-1.2), and the molar ratio of the triethylamine to the dimethylphosphonic chloride is (1.0-1.5):1.

[0012] Optionally, the processing aid consists of a primary antioxidant, a secondary antioxidant, and an internal lubricant, wherein the mass ratio of the primary antioxidant, the secondary antioxidant, and the internal lubricant is (1-5):(2-8):(2-8); The primary antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]; The auxiliary antioxidant is tris(2,4-di-tert-butylphenyl) phosphite; The internal lubricant is N,N'-ethylene bis-stearamide.

[0013] Optionally, the chopped carbon fibers have a length of 3 to 6 mm and a diameter of 5 to 9 μm.

[0014] Secondly, embodiments of this application provide a method for preparing ABS composite material for a mobile phone holder as described in any embodiment of the first aspect, the method comprising the following steps: S1. Place ABS resin, maleic anhydride-grafted hydrogenated styrene-butadiene-styrene block copolymer, nano silica / hyperbranched polyester / ABS masterbatch, N-alkyl-2,2,6,6-tetramethyl-4-aminopiperidine phosphonate and processing aids in a high-speed mixer and mix at room temperature for 5-15 minutes to obtain a premix. S2. The premixed material is added from the main feed port of the twin-screw extruder, short-cut carbon fibers are added from the side feed port, and epoxy-polydimethylsiloxane oligomer is injected through the liquid injection port located at the end of the melting section. The mixture is melt-blended, reacted and extruded at a processing temperature of 180-220°C and a screw speed of 200-400 rpm. After water cooling, pelletizing and drying, the ABS composite material is obtained.

[0015] The technical solutions provided in this application have the following advantages compared with the prior art: This application provides an ABS composite material for mobile phone holders. Through reasonable formulation design and multi-component functional synergy, a composite reinforced and stable system from the molecular interface to the macroscopic scale is constructed without changing the ABS resin itself, thereby simultaneously and effectively improving the rigidity, toughness, wear resistance, anti-slip properties and long-term stability required for mobile phone holders.

[0016] In terms of enhancing rigidity, short-cut carbon fibers are introduced into the formulation as the main load-bearing skeleton. Their high modulus properties directly and significantly improve the overall flexural strength and modulus of the composite material, greatly enhancing its resistance to deformation. At the same time, nano-silica, as nanoscale rigid particles, is uniformly dispersed in the matrix, which can constrain the movement of polymer molecular chains and provide additional reinforcement. The two work together to form a composite reinforcement network spanning the micron and nanoscale.

[0017] The key to improving toughness lies in the role of maleic anhydride-grafted hydrogenated styrene-butadiene-styrene block copolymer. Its rubber-elastomer nature allows it to induce crazing and absorb significant energy under impact, while the grafted maleic anhydride functional groups interact strongly with the SAN phase in the ABS matrix, greatly improving the interfacial adhesion between the elastomer particles and the rigid matrix. This enables impact energy to be efficiently transferred from the matrix to the elastomer phase and dissipated, thus effectively maintaining the material's impact toughness while significantly increasing the stiffness of the carbon fiber, achieving a balance between rigidity and toughness.

[0018] Epoxy-polydimethylsiloxane oligomers play a central role in imparting wear resistance and anti-slip properties. During processing, they react and bond with the ABS matrix, while their low surface energy polysiloxane segments tend to migrate to the product surface, forming a durable, soft, silicone-rich surface layer. This surface layer not only reduces the coefficient of friction, minimizing wear and scratches on the phone's back cover, but also provides adequate grip to prevent the phone from slipping, achieving a balance between wear resistance and anti-slip properties.

[0019] In ensuring long-term stability, the phosphonate ester of N-alkyl-2,2,6,6-tetramethyl-4-aminopiperidine plays a synergistic stabilizing role at the molecular level. This molecule integrates a hindered amine structure with an organophosphorus structure, possessing the dual functions of capturing free radicals and decomposing hydrogen peroxides. Its stabilization efficiency is higher than that of simple compounded stabilizer systems, providing more efficient protection against light, heat, and oxygen aging during processing and long-term use, preventing materials from yellowing and becoming brittle due to aging, thereby maintaining the durability of performance.

[0020] In summary, this application does not solve a single problem with a single component, but rather allows each component to perform its core function at a specific scale (carbon fiber for stiffening, grafted elastomer for toughening, reactive organosilicon for surface improvement, and synergistic stabilizer for anti-aging). Through good interfacial bonding (such as grafted functional groups) and process design, these functions promote each other rather than cancel each other out, ultimately achieving the stringent requirements for the comprehensive performance of materials in mobile phone holders. Attached Figure Description

[0021] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application.

[0022] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0023] Figure 1 This is a schematic flowchart illustrating the preparation method of ABS composite material for mobile phone holders provided in this application embodiment. Detailed Implementation

[0024] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0025] This application provides an ABS composite material for a mobile phone holder. By weight, the ABS composite material is composed of the following raw materials: ABS resin: 100 parts, maleic anhydride-grafted hydrogenated styrene-butadiene-styrene block copolymer: 8-15 parts, epoxy-polydimethylsiloxane oligomer: 2-5 parts, chopped carbon fiber: 5-10 parts, nano-silica / hyperbranched polyester / ABS masterbatch: 2-6 parts, N-alkyl-2,2,6,6-tetramethyl-4-aminopiperidine phosphonate: 0.3-1.0 parts, and processing aids: 0.5-1.5 parts.

[0026] The core of the ABS composite material system design in this application lies in constructing a synergistic network from the molecular, nano-, and micro-levels by introducing multi-component, multi-scale functional additives without altering the chemical structure of the ABS resin itself. This systematically addresses the comprehensive requirements of mobile phone holders for high rigidity, high toughness, wear resistance, anti-slip properties, and long-term stability. Specifically, the roles of each raw material are as follows: ABS resin matrix: As a continuous phase, it is itself a two-phase structure consisting of styrene-acrylonitrile copolymer (SAN) and polybutadiene (PB) rubber particles dispersed within it. SAN provides rigidity, strength, and processing flowability, while PB particles absorb impact energy by inducing crazes and shear bands, providing toughness. However, the rigidity, heat resistance, and surface hardness of pure ABS need improvement.

[0027] Maleic anhydride-grafted SEBS: Its core function is as a "molecular bridge" and "interfacial compatibilizer." The hydrogenated butadiene segments of SEBS have an affinity for the PB rubber in ABS, while the grafted maleic anhydride (MAH) functional groups can generate strong dipole-dipole interactions with the cyano groups (-C≡N) in the SAN phase of ABS during melt processing, and may even undergo slight chemical reactions. This greatly enhances the originally weakly bonded SAN-PB two-phase interface, allowing stress energy to be transferred more effectively from the rigid SAN phase to the rubber phase for dissipation, improving impact toughness while minimizing damage to rigidity.

[0028] Epoxy-based polydimethylsiloxane oligomers: These oligomers have a number-average molecular weight of 1000-5000 and are reactive surface functional agents. One end of the molecule is a flexible polydimethylsiloxane chain (organosilicon), and the other end is an active epoxy group. At high temperatures during later stages of processing, the epoxy groups can undergo a mild ring-opening reaction with the cyano groups or end groups in the SAN phase of ABS, forming chemical bonds. This allows the low surface energy organosilicon segments to be chemically anchored in the matrix and tend to migrate to the surface of the product, forming a durable, wear-resistant, low-friction coefficient organosilicon-rich layer, fundamentally improving the feel and scratch resistance.

[0029] Short-cut carbon fibers serve as a "macroscopic reinforcing skeleton." Their ultra-high modulus and strength directly act as the main load-bearing structure, significantly improving the tensile / flexural strength, modulus, and creep resistance of composite materials. The orientation and distribution of fibers in the matrix constitute the structural basis for the material's rigidity.

[0030] Nano-silica / hyperbranched polyester / ABS masterbatch: This is a "nanoscale reinforcement and stabilization unit." Hyperbranched polyester, through its numerous terminal functional groups (such as hydroxyl groups), strongly interacts with the surface of nano-silica (particle size 10-50 nm), achieving "single-particle" coating and preventing nanoparticle aggregation. The uniformly dispersed nano-silica acts as "hard points," enhancing the matrix's hardness and wear resistance. More importantly, it acts as a stress concentration point in the SAN matrix, inducing numerous tiny crazes that absorb a large amount of energy and, in synergy with carbon fibers and rubber, preventing crazes from developing into destructive cracks.

[0031] N-alkyl-2,2,6,6-tetramethyl-4-aminopiperidine phosphonate: This is a molecularly designed "multifunctional synergistic stabilizer." Its molecule integrates the structures of a "hindered amine" and an "organophosphine." The hindered amine moiety is a classic free radical scavenger, effectively terminating polymer free radicals generated during processing and use, preventing chain degradation. The organophosphine moiety can also function as a decomposition agent for hydrogen peroxide and has potential flame-retardant synergistic effects. The amine groups in the molecule can also interact with the MAH functional groups and epoxy groups in the system, to a certain extent "crosslinking" and stabilizing the entire multiphase interfacial network, improving the overall thermo-oxidative stability of the structure.

[0032] Processing aids: Primary / secondary antioxidants (such as 1010 / 168) provide primary and secondary antioxidant protection and inhibit melt degradation; internal lubricants (such as EBS) improve flowability, promote dispersion of components, and reduce wear on screws and molds.

[0033] More importantly, the core of the innovation of this ABS composite material system lies in the fact that it is not a simple physical blend of multiple components, but rather a comprehensive performance that cannot be achieved by a single component through careful molecular and structural design. During processing and application, each component forms a closely linked cross-scale synergistic reinforcement and stabilization network at different scales (molecular interface, nano, micro, macro), thereby systematically achieving the comprehensive performance that a single component cannot achieve.

[0034] First, it achieves excellent rigidity-toughness synergy in mechanical properties. Short-cut carbon fibers, acting as a macroscopically rigid skeleton, directly bear and significantly enhance the overall modulus and strength of the material. Maleic anhydride-grafted SEBS, acting as a molecular-scale "bridge," significantly strengthens the interface between the brittle SAN phase and the tough rubber phase in ABS through the strong interaction between its functional groups and the matrix, ensuring efficient stress transfer and allowing the rubber phase to fully exert its toughening effect. Nanoscale silica, as uniformly dispersed hard particles at the nanoscale, can both induce numerous microcracks to absorb energy and prevent crack propagation. These three components together construct a complete stress transfer and multiple dissipation pathway from "fiber skeleton → rigid matrix → nanoparticles → toughened interface," thereby effectively ensuring and even enhancing the material's impact toughness while improving strength, resolving the contradiction of "increasing rigidity inevitably leads to a loss of toughness" in traditional reinforced materials.

[0035] Secondly, a long-lasting synergistic mechanism is established between surface and bulk properties. The key innovation of epoxy-polydimethylsiloxane oligomers as reactive surface functional agents lies in their anchoring through chemical bonding between epoxy groups and the ABS matrix. This allows low-surface-energy organosilicon segments to be persistently and stably enriched on the product surface, providing excellent wear resistance and anti-slip feel. More importantly, this chemical anchoring mechanism avoids the easy precipitation of small-molecule additives. Even if the surface layer is worn away, the functional agents bonded in the bulk can continue to replenish, achieving long-lasting surface functionality while avoiding the potential weakening of bulk mechanical properties by physically migrating additives.

[0036] Furthermore, it provides molecular-level synergistic protection for the long-term stability of the material. The independently developed N-alkyl-2,2,6,6-tetramethyl-4-aminopiperidine phosphonate integrates two stabilization mechanisms—hindered amine (free radical capture) and organophosphine (hydrogen peroxide decomposition)—within its molecule, resulting in a synergistic anti-aging effect that is more efficient than simple blends of single stabilizers. In addition, the active groups in this stabilizer molecule can interact with the anhydride groups of SEBS-g-MAH and the epoxy groups of epoxy-based silicone oil in the system, thereby helping to stabilize the interface of the entire multiphase system and improving the overall structural stability and performance retention of the composite material under thermal, oxygen, and photo-aging conditions.

[0037] Finally, a high degree of synergy was achieved between processing technology and final performance. Nano-silica, pre-dispersed in hyperbranched polyester and formulated into masterbatch, fundamentally ensures its uniform nanoscale dispersion in the matrix, a prerequisite for all nano-reinforcing effects. The unique "end-injection" processing technology allows reactive organosilicon to contact the matrix at the end of melt blending and undergo a controllable in-situ reaction, precisely controlling the degree of interfacial chemical modification. This achieves surface functionality while avoiding the negative impacts on processing flowability and material toughness caused by excessive crosslinking.

[0038] In summary, this system tightly integrates its functional components through mechanisms such as chemical bonding, physical entanglement, and stress field coupling, forming an integrated composite material system that is internally strengthened, has robust interfaces, functionalized surfaces, and overall stability. All design mechanisms are based on reliable polymer physics and chemistry principles, enabling the material to simultaneously meet the stringent requirements of mobile phone holders for high rigidity, high toughness, excellent surface feel, long-term wear resistance, and long-term durability. In some embodiments, the preparation method of maleic anhydride-grafted hydrogenated styrene-butadiene-styrene block copolymer includes the following steps: S101. Hydrogenated styrene-butadiene-styrene block copolymer, maleic anhydride monomer and dicumyl peroxide are stirred and mixed in a high-speed mixer at 60-80°C for 5-15 minutes to obtain a premix. S102. The premixed material is fed into a twin-screw extruder and subjected to a grafting reaction under melting temperature and shearing action. After water cooling and pelletizing, maleic anhydride-grafted hydrogenated styrene-butadiene-styrene block copolymer is obtained. The mass ratio of hydrogenated styrene-butadiene-styrene block copolymer, maleic anhydride monomer, and dicumyl peroxide is 100:(0.8~2.0):(0.1~0.4). The processing temperature of the twin-screw extruder is 170–190℃, the screw speed is 80–200 rpm, and the material residence time is 1–3 min. The grafting rate of maleic anhydride-grafted hydrogenated styrene-butadiene-styrene block copolymer is 0.8–1.2%.

[0039] It should be noted that the principle of the preparation method of maleic anhydride-grafted SEBS is the classic melt free radical grafting. In step S101, premixing, through stirring at 60–80°C, moderately softens the SEBS particles, ensuring that the liquid maleic anhydride monomer and dicumyl peroxide initiator can uniformly penetrate and adhere to the surface and interior of the SEBS, laying the foundation for subsequent homogeneous reactions. Step S102, the melt reaction, is the core of this process. The twin-screw extruder provides continuous melt temperature and shear force. The temperature window of 170–190°C ensures complete melting of the SEBS and efficient decomposition of the initiator to generate free radicals, while effectively inhibiting excessive volatilization and thermal decomposition of the maleic anhydride monomer. The screw speed of 80–200 rpm and the residence time of 1–3 min work synergistically to provide sufficient shear to promote mixing and reaction while strictly controlling the material's heating process, preventing degradation of the polymer matrix due to prolonged exposure to high temperature and high shear. A grafting rate of 0.8% to 1.2% is a key indicator for balancing performance and process. This range of grafting amount is sufficient to introduce enough polar functional groups into the SEBS molecular chain, thereby generating a strong interaction with the SAN phase of ABS. At the same time, it avoids the possibility that the SEBS itself may lose elasticity or cross-link due to excessive grafting rate.

[0040] In some embodiments, the preparation method of epoxy-polydimethylsiloxane oligomers includes the following steps: S201. Under vacuum conditions of 90-110℃, hydrogen-containing silicone oil and allyl glycidyl ether are dehydrated for 1-2 hours to obtain a mixture. S202. Under inert gas protection, the mixture is cooled to 80-90°C, then Karstedt catalyst is added, and the mixture is stirred at 80-90°C for 4-8 hours to obtain epoxy-polydimethylsiloxane oligomer. The molar ratio of the silicon-hydrogen bonds in the hydrogen-containing silicone oil to the carbon-carbon double bonds in the allyl glycidyl ether is 1:(1.0~1.2). The mass of Karstedt catalyst is 5 to 50 ppm of the mass of hydrogen-containing silicone oil; The epoxy value of epoxy-dimethylsiloxane oligomers is 0.05 to 0.15.

[0041] It should be noted that the preparation of epoxy-polydimethylsiloxane oligomers is based on a highly efficient and selective platinum-catalyzed hydrosilylation reaction. The dehydration treatment in step S201 is crucial; continuous treatment at 90–110°C under vacuum for 1–2 hours thoroughly removes trace amounts of moisture from the hydrogen-containing silicone oil and allyl glycidyl ether in the raw materials, preventing the subsequent addition of the valuable platinum catalyst (Karstedt catalyst) from being deactivated due to poisoning. The catalytic addition in step S202 is key to constructing the target molecule. The reaction is carried out under an inert atmosphere and at a mild temperature of 80–90°C. This temperature ensures a reasonable reaction rate while maximizing the stability of the epoxy groups, preventing side reactions such as ring-opening. The molar ratio of silicon-hydrogen bonds to carbon-carbon double bonds is controlled at 1:(1.0–1.2), meaning a slight excess of allyl glycidyl ether. This design drives the Si-H bonds in the relatively expensive hydrogen-containing silicone oil to react as completely as possible, improving the utilization rate of the raw materials. The catalyst dosage was 5–50 ppm of the hydrogen-containing silicone oil mass, demonstrating the extremely high catalytic efficiency of the Karstedt catalyst, where a rapid and complete reaction can be achieved with a small amount of addition. The final product had an epoxy value of 0.05–0.15, indicating the successful introduction of a moderate concentration of reactive epoxy groups, which provided sufficient activity for reaction with the ABS matrix while avoiding material embrittlement due to excessive functional group density.

[0042] In some embodiments, the preparation method of nano-silica / hyperbranched polyester / ABS masterbatch includes the following steps: S301. Under nitrogen protection, trimethylolpropane, 2,2-dimethylolpropionic acid and p-toluenesulfonic acid catalyst are subjected to melt polycondensation reaction at 140-160°C for 6-10 hours to obtain hydroxyl-terminated hyperbranched polyester. S302. Mix nano-silica and hyperbranched polyester at 80-100℃ for 10-30 min to coat the surface of nano-silica with hyperbranched polyester to obtain pretreated composite powder. S303. Pretreated composite powder and ABS resin are added to a twin-screw extruder for melt blending and extrusion granulation to obtain nano-silica / hyperbranched polyester / ABS masterbatch. The twin-screw extruder has a processing temperature of 180–220℃ and a screw speed of 200–400 rpm.

[0043] In some embodiments, the molar ratio of trimethylolpropane to 2,2-dimethylolpropionic acid is 1:(15-30); The mass of the p-toluenesulfonic acid catalyst is 1.0–3.0% of the mass of 2,2-dimethylolpropionic acid; The mass ratio of nano-silica to hyperbranched polyester is 100:(5-20); The mass ratio of pretreated composite powder to ABS resin is (20-40):(60-80).

[0044] It should be noted that the preparation method of nano-silica / hyperbranched polyester / ABS masterbatch aims to solve the problem of nanoparticle aggregation once and for all through a "pre-coating-masterbatch" strategy. Step S301 is the synthesis of hyperbranched polyester, which adopts a melt polycondensation method with trimethylolpropane as the core and 2,2-dimethylolpropionic acid as the AB2 monomer. The reaction temperature of 140-160℃ and the reaction time of 6-10h ensure that highly branched polymers with terminal hydroxyl-rich structures are gradually formed under mild conditions. The molar ratio of 1:(15-30) determines the final molecular weight and degree of branching of the hyperbranched polyester, thereby controlling its dispersion ability. Step S302 is the core pretreatment, in which nano-silica and hyperbranched polyester are mixed at 80-100℃ for 10-30min. This temperature helps the hyperbranched polyester molecular chain movement, allowing it to form strong physical adsorption and hydrogen bonding with the nanoparticle surface through a large number of terminal hydroxyl groups, achieving single-particle-level coating and forming a stable "core-shell" structured composite powder. In step S303, the masterbatch is produced by melting and granulating the pretreated powder with the ABS carrier at 180–220°C. This process "fixes" the coated nanoparticles within the ABS matrix, creating a high-concentration masterbatch. The mass ratio of the pretreated powder to the ABS resin is (20–40):(60–80), ensuring that the masterbatch has sufficient nanoparticle content so that an effective number of nanoparticles can be introduced with a small amount during final compounding, without affecting the overall processing flowability.

[0045] In some embodiments, the preparation method of N-alkyl-2,2,6,6-tetramethyl-4-aminopiperidine phosphonate includes the following steps: S401. In the presence of potassium carbonate, (2,2,6,6-tetramethyl-piperidin-4-yl)-methylamine is reacted with iodoethane at 60-110 °C for 4-12 h to obtain an intermediate; S402. In the presence of the acid-binding agent triethylamine, the intermediate is subjected to a phosphonylation reaction with dimethylphosphonic chloride at room temperature for 1-3 hours to obtain a reaction solution containing the crude product. S403. The reaction solution was washed, separated, dried and concentrated, and then purified to obtain N-alkyl-2,2,6,6-tetramethyl-4-aminopiperidine phosphonate.

[0046] In some embodiments, the molar ratio of (2,2,6,6-tetramethyl-piperidin-4-yl)-methylamine to iodoethane is 1:(1.0 to 1.5); The molar ratio of the intermediate to dimethylphosphonic chloride is 1:(1.0–1.2), and the molar ratio of triethylamine to dimethylphosphonic chloride is (1.0–1.5):1.

[0047] It should be noted that the synthetic route for phosphonates of N-alkyl-2,2,6,6-tetramethyl-4-aminopiperidine precisely constructs molecules possessing both hindered amine and organophosphine structures in a two-step process. Step S401 is N-alkylation, involving the reaction of commercially available piperidinamine with iodoethane in the presence of potassium carbonate. Iodoethane was chosen due to its excellent reactivity. The temperature range of 60–110 °C covers conditions from mild to forced reactions, and the reaction time of 4–12 h ensures complete conversion. A molar ratio of 1:(1.0–1.5) with excess iodoethane drives the amine reaction towards completion. Step S402 is phosphonylation, which is crucial for constructing the phosphorus-nitrogen co-synergistic structure. The amine intermediate obtained in the previous step is reacted with dimethylphosphonyl chloride in the presence of the acid-binding agent triethylamine. The reaction is carried out at a low temperature of 0–30 °C for 1–3 h, which effectively suppresses side reactions (such as over-alkylation) that may be caused by exothermic reactions and the basicity of the amine, thereby improving the selectivity of the target product. Molar ratio control (intermediate: dimethylphosphonochloride: triethylamine) ensures the full action of the reactants, while the acid-binding agent effectively neutralizes the generated HCl.

[0048] In some embodiments, the processing aid consists of a primary antioxidant, a secondary antioxidant, and an internal lubricant, wherein the mass ratio of the primary antioxidant, the secondary antioxidant, and the internal lubricant is (1-5):(2-8):(2-8); The main antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]; The auxiliary antioxidant is tris(2,4-di-tert-butylphenyl) phosphite; The internal lubricant is N,N'-ethylene bis-stearamide.

[0049] It should be noted that the processing aid adopts a classic compound system of primary antioxidant 1010, secondary antioxidant 168 and internal lubricant EBS, with a mass ratio of (1-5):(2-8):(2-8). This system can provide comprehensive stable protection from free radical capture to hydroperoxide decomposition during material processing and use, and significantly improve melt flowability.

[0050] In some embodiments, the chopped carbon fibers have a length of 3–6 mm and a diameter of 5–9 μm.

[0051] It should be noted that the chopped carbon fibers are 3-6 mm in length and 5-9 μm in diameter, which can form an effective reinforcing network in composite materials and significantly improve rigidity. At the same time, their aspect ratio ensures that they will not become excessively entangled or broken due to excessive length in injection molding screws, thus achieving the best balance between processing flowability and final mechanical properties.

[0052] Figure 1 This is a schematic flowchart illustrating the preparation method of ABS composite material for mobile phone holders provided in this application embodiment.

[0053] Based on a general inventive concept, such as Figure 1 As shown in the embodiments of this application, a method for preparing ABS composite material for a mobile phone holder according to any of the above embodiments is provided. The method includes the following steps: S1. Place ABS resin, maleic anhydride-grafted hydrogenated styrene-butadiene-styrene block copolymer, nano silica / hyperbranched polyester / ABS masterbatch, N-alkyl-2,2,6,6-tetramethyl-4-aminopiperidine phosphonate and processing aids in a high-speed mixer and mix at room temperature for 5-15 minutes to obtain a premix. S2. The premixed material is added from the main feed port of the twin-screw extruder, and short-cut carbon fibers are added from the side feed port. The epoxy-polydimethylsiloxane oligomer is injected through the liquid injection port located at the end of the melting section. The mixture is melt-blended, reacted and extruded at a processing temperature of 180-220°C and a screw speed of 200-400 rpm. After water cooling, pelletizing and drying, the ABS composite material is obtained.

[0054] The design of this preparation method profoundly reflects the precise control of the processing characteristics of multi-component, multi-functional composite materials. Its two-step process is not a simple mixing and plasticizing, but aims to maximize the function of each component and ensure the synergistic effect by using a step-by-step, zone-based feeding strategy.

[0055] The core function of the first step (S1), room-temperature premixing, is to achieve a macroscopically uniform distribution of all solid components before entering the high-temperature, high-shear melt processing. This step physically mixes the ABS resin matrix, toughening agent (SEBS-g-MAH), nano-reinforcing masterbatch, synergistic stabilizer, and processing aids at room temperature in a high-speed mixer. This process is crucial because it ensures that key components, which are added in small quantities but have a significant impact on performance (especially the self-made stabilizer and nano-masterbatch), achieve a relatively uniform spatial distribution in the large-scale ABS resin. This lays a solid foundation for achieving more efficient and thorough micro-dispersion in the subsequent screw extruder with limited residence time, avoiding performance inconsistencies caused by excessively high or low local concentrations.

[0056] The second step (S2), melt blending and reactive extrusion, is the core and innovation of this preparation method. It optimizes material properties through sophisticated "branched feeding" and "reaction timing control." This step is designed to be completed in a twin-screw extruder, and its function is multi-layered: First, the premix is ​​added through the main feed port, allowing the bulk material to be gradually plasticized in the screw's conveying and melting sections, forming a homogeneous melt. Second, the addition of chopped carbon fibers from the side feed port located in the downstream of the melting section is a key process design. This aims to allow the carbon fibers to avoid the high-shear section at the front end, where the solid-liquid phase transition is underway, and to be introduced only after the matrix resin has largely melted. This significantly reduces excessive shearing and breakage of the fibers by the screw, maximizing the preservation of the initial fiber length and aspect ratio, thereby ensuring its effectiveness as a macroscopic reinforcing skeleton.

[0057] Even more ingenious is the injection of epoxy-polydimethylsiloxane oligomers through a liquid injection port located at the end of the molten section. This design is the key to realizing the "reactive surface functionalization" concept of this scheme. The principle is to allow the reactive silicone liquid to come into contact with the high-temperature melt and mix instantaneously at the very last moment before being extruded from the die head, after the matrix resin has been completely melted and homogenized. This brings two core advantages: first, it achieves "in-situ reaction," where the epoxy groups of the silicone can undergo a controlled chemical reaction with the cyano groups in the ABS melt at a processing temperature of 180–220°C, forming chemical bonds; second, it achieves "precise control of the degree of reaction," as the extremely short time from injection to extrusion cooling effectively suppresses side reactions such as excessive crosslinking, keeping the reaction within a suitable range (typically a grafting rate of <5%), thus imparting surface functionality to the material without affecting the system's flowability and bulk toughness. The entire melt blending process is carried out at a screw speed of 200-400 rpm, which provides sufficient shear force to ensure the dispersion of carbon fibers and the final distribution of nanoparticles. Finally, after cooling and granulation, composite material particles with uniform properties are obtained.

[0058] In summary, this preparation method, through a progressive process design of "room temperature pre-dispersion - melt partitioned feeding - end-stage in-situ reaction," ensures the integrity (carbon fiber) and dispersion (nanoparticles) of the multi-scale reinforcing phase at the physical level, and achieves precise and efficient interface modification (SEBS-g-MAH) and surface functionalization (epoxy silicone oil) reactions at the chemical level. The synergistic effect of the entire process is a key bridge in transforming the aforementioned molecular design into a physical material with comprehensive properties of high stiffness, high toughness, wear resistance, and stability.

[0059] In summary, the ABS composite material prepared in this application is a product of systematic and integrated design, from its molecular design and multiphase structure to its final comprehensive performance, in response to the stringent requirements of the specific application scenario of mobile phone holders.

[0060] First, the material's superior rigidity-toughness synergy provides a safe and reliable mechanical foundation for the phone holder. A phone holder needs to possess sufficient rigidity to stably support phones of different sizes and weights and resist deformation (creep resistance) during long-term use; it also needs excellent toughness to withstand accidental drops or impacts and prevent brittle fracture. This material constructs a multi-layered energy dissipation network through macroscopic reinforcement with short-chopped carbon fibers, nano-scale stiffening and crazing induction with nano-silica, and toughening with interface-strengthened SEBS-g-MAH. This allows the material to achieve high strength and high modulus comparable to engineering plastics while retaining the good impact toughness of the ABS matrix, thus ensuring that the holder is both stable and durable during use, and not easily damaged by accident.

[0061] Secondly, the material directly addresses two major user experience pain points of phone holders through reactive surface functionalization technology: wear resistance and slip resistance, and a comfortable feel. Traditional surface treatments (such as spraying) are prone to wear and peeling, while the epoxy-polydimethylsiloxane oligomers in this material are chemically bonded and anchored in the matrix, migrating to the surface to form a durable, soft, silicone-rich layer. This structure endows the product surface with an inherent low coefficient of friction and a delicate touch, effectively preventing scratches on the phone's back cover from the holder's clamping area, while providing sufficient friction to prevent the phone from slipping, and this performance can be maintained even after long-term use.

[0062] Furthermore, the material's excellent dimensional stability and durability ensure the long-term precision and reliability of the phone holder. The addition of carbon fiber and nanoparticles significantly reduces the material's coefficient of thermal expansion and improves its heat resistance, making the holder less prone to deformation in temperature-changing environments such as outdoors or in vehicles, thus maintaining clamping accuracy. More importantly, the independently developed phosphorus-nitrogen synergistic stabilizer provides long-lasting molecular-level protection for the entire multiphase system, effectively inhibiting the aging and degradation of the material under the influence of light, heat, and oxygen. This avoids problems such as yellowing, brittleness, and performance degradation that easily occur in ordinary plastic holders after long-term use, greatly extending the product's lifespan.

[0063] Finally, while possessing the aforementioned high performance, the material also retains good processability. Through optimized formulation and process design (such as highly dispersed masterbatch, internal lubricant, and specific processing windows), this composite material can be efficiently and precisely molded through conventional processes such as injection molding, meeting the design requirements of complex structures and delicate clips in mobile phone brackets, and achieving stable mass production.

[0064] The present application is further illustrated below with reference to specific embodiments. Experimental methods in the following embodiments that do not specify specific conditions are generally determined according to national standards / industry standards / the disclosure herein; if there are no corresponding national standards / industry standards / the disclosure herein, they are performed according to generally accepted international standards, conventional conditions, or conditions recommended by the manufacturer.

[0065] Example 1 This embodiment provides the raw material composition of the ABS composite material, which is as follows, by weight: ABS resin (brand name PA-757): 100 parts, maleic anhydride-grafted hydrogenated styrene-butadiene-styrene block copolymer: 8 parts, epoxy-polydimethylsiloxane oligomer: 2 parts, short-cut carbon fiber (length in the range of 3-6 mm, diameter in the range of 5-9 μm, purchased from Yancheng Xiang Sheng Carbon Fiber Technology Co., Ltd.): 5 parts, nano-silica / hyperbranched polyester / ABS masterbatch: 2 parts, N-alkyl-2,2,6,6-tetramethyl-4 -Aminopiperidine phosphonate: 0.3 parts, processing aid: 0.5 parts. The processing aid consists of the main antioxidant pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (CAS6683-19-8), the auxiliary antioxidant tris(2,4-di-tert-butylphenyl) phosphite (CAS31570-04-4), and the internal lubricant N,N'-ethylene bis-stearamide (CAS110-30-5), with a mass ratio of 1:2:2.

[0066] The preparation method of maleic anhydride-grafted hydrogenated styrene-butadiene-styrene block copolymer includes the following steps: Hydrogenated styrene-butadiene-styrene block copolymer (SEBS), maleic anhydride monomer (CAS108-31-6), and dicumyl peroxide (DCP, CAS80-43-3) are mixed in a high-speed mixer at a mass ratio of 100:0.8:0.1 at 60°C for 5 minutes to obtain a premix. This premix is ​​then fed into a twin-screw extruder and subjected to a melt grafting reaction at a processing temperature of 170°C and a screw speed of 80 rpm, with the material residence time controlled to approximately 1 minute. After water cooling, pelletizing, and drying, maleic anhydride-grafted SEBS with a grafting rate of 0.8% is obtained.

[0067] The preparation method of epoxy-polydimethylsiloxane oligomers includes the following steps: Hydrogen-containing silicone oil (CAS63148-57-2) and allyl glycidyl ether (CAS106-92-3) are weighed at a molar ratio of 1:1.0 between silicon-hydrogen bonds and carbon-carbon double bonds. The mixture is dehydrated at 90°C under vacuum for 1 hour. Subsequently, under nitrogen protection, the mixture is cooled to 80°C, and 5 ppm of Karstedt catalyst (platinum-vinylsiloxane complex, CAS68478-92-2) by mass of the hydrogen-containing silicone oil is added. The mixture is stirred at 80°C for 4 hours. After the reaction, epoxy-polydimethylsiloxane oligomers with an epoxy value of 0.05 are obtained.

[0068] The preparation method of nano-silica / hyperbranched polyester / ABS masterbatch includes the following steps: First, prepare hyperbranched polyester: trimethylolpropane (CAS77-99-6) and 2,2-dimethylolpropionic acid (DMPA, CAS4767-03-7) are mixed at a molar ratio of 1:15, and 1.0% by mass of p-toluenesulfonic acid catalyst (CAS104-15-4) of DMPA is added. The mixture is subjected to melt polycondensation reaction at 140℃ for 6 hours under nitrogen protection to obtain hydroxyl-terminated hyperbranched polyester. Second, nano-silica (CAS7631-86-9, particle size 20-50nm) and the above hyperbranched polyester are mixed at a mass ratio of 100:5 at 80℃ for 10 minutes to fully coat the nano-silica with the hyperbranched polyester, resulting in a pretreated composite powder. Finally, the pretreated composite powder and ABS resin were added to a twin-screw extruder at a mass ratio of 20:80, and melt-blended and extruded at a processing temperature of 180℃ and a screw speed of 200rpm to obtain nano-silica / hyperbranched polyester / ABS masterbatch.

[0069] The preparation method of N-alkyl-2,2,6,6-tetramethyl-4-aminopiperidine phosphonate comprises the following steps: First, an N-alkylation reaction is carried out: (2,2,6,6-tetramethyl-piperidin-4-yl)-methylamine (i.e., N,2,2,6,6-pentamethylpiperidin-4-amine, CAS62995-79-3) and iodoethane (CAS75-03-6) are weighed in a molar ratio of 1:1.0 and reacted at 60°C for 4 h in the presence of potassium carbonate (CAS584-08-7) to obtain an amine intermediate. Then, a phosphonylation reaction is carried out: the intermediate obtained in the previous step is weighed in a molar ratio of 1:1.0 with dimethylphosphonochloride (CAS813-77-4) and reacted at 0-30°C (room temperature) for 1 h in the presence of 1.0 molar amount of the acid-binding agent triethylamine (CAS121-44-8) to obtain a crude product reaction solution. Finally, the reaction solution was washed, separated, dried, and concentrated, and then purified by column chromatography to obtain the dimethylphosphonate of the target product N-ethyl-2,2,6,6-tetramethyl-4-aminopiperidine.

[0070] Based on the raw material composition of the ABS composite material described above, this embodiment also provides a method for preparing the ABS composite material, including the following steps: S1. Weigh the ABS resin, maleic anhydride-grafted SEBS, nano masterbatch, N-alkyl-2,2,6,6-tetramethyl-4-aminopiperidine phosphonate and processing aids according to the formula and place them in a high-speed mixer. Mix at room temperature for 5 minutes to obtain a premix.

[0071] S2. The obtained premix is ​​added through the main feed port of the twin-screw extruder, while chopped carbon fibers are added through the side feed port. Epoxy-polydimethylsiloxane oligomer is injected through the liquid injection port located at the end of the melt section. The processing temperature of the twin-screw extruder is set to 180°C and the screw speed to 200 rpm for melt blending, reaction, and extrusion. The extruded strips are water-cooled, pelletized, and dried at 80°C for 4 hours to obtain the ABS composite material particles for mobile phone holders in this embodiment.

[0072] Example 2 This embodiment provides the raw material composition of the ABS composite material, which is as follows, by weight: ABS resin: 100 parts, maleic anhydride-grafted hydrogenated styrene-butadiene-styrene block copolymer: 12 parts, epoxy-polydimethylsiloxane oligomer: 3 parts, short-cut carbon fiber (length in the range of 3-6 mm, diameter in the range of 5-9 μm): 8 parts, nano-silica / hyperbranched polyester / ABS masterbatch: 4 parts, N-alkyl-2,2,6,6-tetramethyl-4-aminopiperidine phosphonate: 0.6 parts, processing aids: 1.0 part. The processing aids consist of the main antioxidant pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], the auxiliary antioxidant tris(2,4-di-tert-butylphenyl) phosphite, and the internal lubricant N,N'-ethylene bis-stearamide, with a mass ratio of 3:5:5.

[0073] The preparation method of maleic anhydride-grafted hydrogenated styrene-butadiene-styrene block copolymer includes the following steps: Hydrogenated styrene-butadiene-styrene block copolymer (SEBS), maleic anhydride monomer, and dicumyl peroxide (DCP) are mixed in a high-speed mixer at a mass ratio of 100:1.5:0.2 at 70°C for 10 minutes to obtain a premix. This premix is ​​then fed into a twin-screw extruder and subjected to a melt grafting reaction at a processing temperature of 180°C and a screw speed of 140 rpm, with the material residence time controlled at approximately 2 minutes. After water cooling, pelletizing, and drying, maleic anhydride-grafted SEBS with a grafting rate of 1.0% is obtained.

[0074] The preparation method of epoxy-polydimethylsiloxane oligomers includes the following steps: Hydrogen-containing silicone oil and allyl glycidyl ether are weighed at a molar ratio of 1:1.1 (silicon-hydrogen bonds to carbon-carbon double bonds). The mixture is dehydrated at 100°C under vacuum for 1.5 h. Subsequently, under nitrogen protection, the mixture is cooled to 85°C, and 20 ppm (by mass of the hydrogen-containing silicone oil) of Karstedt catalyst (platinum-vinylsiloxane complex) is added. The mixture is stirred at 85°C for 6 h. After the reaction, epoxy-polydimethylsiloxane oligomers with an epoxy value of 0.10 are obtained.

[0075] The preparation method of nano-silica / hyperbranched polyester / ABS masterbatch includes the following steps: First, prepare hyperbranched polyester: trimethylolpropane and 2,2-dimethylolpropionic acid (DMPA) are mixed at a molar ratio of 1:22, and 2.0% by weight of p-toluenesulfonic acid catalyst is added. The mixture is then subjected to melt polycondensation at 150°C for 8 hours under nitrogen protection to obtain hydroxyl-terminated hyperbranched polyester. Second, nano-silica (particle size 20-50 nm) and the above-mentioned hyperbranched polyester are mixed at a mass ratio of 100:12 at 90°C for 20 minutes to ensure that the hyperbranched polyester fully coats the nano-silica, resulting in a pretreated composite powder. Finally, the pretreated composite powder and ABS resin are added to a twin-screw extruder at a mass ratio of 30:70. The mixture is then melt-blended, extruded, and granulated at a processing temperature of 200°C and a screw speed of 300 rpm to obtain nano-silica / hyperbranched polyester / ABS masterbatch.

[0076] The preparation method of N-alkyl-2,2,6,6-tetramethyl-4-aminopiperidine phosphonate includes the following steps: First, an N-alkylation reaction is carried out: (2,2,6,6-tetramethyl-piperidin-4-yl)-methylamine and iodoethane are weighed at a molar ratio of 1:1.2 and reacted at 80°C for 8 h in the presence of potassium carbonate to obtain an amine intermediate. Then, a phosphonylation reaction is carried out: the intermediate obtained in the previous step is weighed with dimethylphosphonochloride at a molar ratio of 1:1.1 and reacted at room temperature for 2 h in the presence of 1.2 molar amounts of triethylamine as an acid-binding agent to obtain a crude product reaction solution. Finally, the reaction solution is washed, separated, dried, concentrated, and purified by column chromatography to obtain the target product, N-ethyl-2,2,6,6-tetramethyl-4-aminopiperidine dimethylphosphonate.

[0077] Based on the raw material composition of the ABS composite material described above, this embodiment also provides a method for preparing the ABS composite material, including the following steps: S1. Weigh the ABS resin, maleic anhydride-grafted SEBS, nano masterbatch, N-alkyl-2,2,6,6-tetramethyl-4-aminopiperidine phosphonate and processing aids according to the formula and place them in a high-speed mixer. Mix at room temperature for 10 minutes to obtain a premix.

[0078] S2. The obtained premix is ​​added through the main feed port of the twin-screw extruder, while chopped carbon fibers are added through the side feed port. Epoxy-polydimethylsiloxane oligomer is injected through the liquid injection port located at the end of the melt section. The processing temperature of the twin-screw extruder is set to 200°C and the screw speed to 300 rpm for melt blending, reaction, and extrusion. The extruded strips are water-cooled, pelletized, and dried at 80°C for 4 hours to obtain the ABS composite material particles for mobile phone holders in this embodiment.

[0079] Example 3 This embodiment provides the raw material composition of the ABS composite material, which is as follows, by weight: ABS resin: 100 parts, maleic anhydride-grafted hydrogenated styrene-butadiene-styrene block copolymer: 15 parts, epoxy-polydimethylsiloxane oligomer: 5 parts, short-cut carbon fiber (length in the range of 3-6 mm, diameter in the range of 5-9 μm): 10 parts, nano-silica / hyperbranched polyester / ABS masterbatch: 6 parts, N-alkyl-2,2,6,6-tetramethyl-4-aminopiperidine phosphonate: 1.0 part, processing aid: 1.5 parts. The processing aid consists of the main antioxidant pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], the auxiliary antioxidant tris(2,4-di-tert-butylphenyl) phosphite, and the internal lubricant N,N'-ethylene bis-stearamide, with a mass ratio of 5:8:8.

[0080] The preparation method of maleic anhydride-grafted hydrogenated styrene-butadiene-styrene block copolymer includes the following steps: Hydrogenated styrene-butadiene-styrene block copolymer (SEBS), maleic anhydride monomer, and dicumyl peroxide (DCP) are mixed in a high-speed mixer at a mass ratio of 100:2.0:0.4 at 80°C for 15 minutes to obtain a premix. This premix is ​​then fed into a twin-screw extruder and subjected to a melt grafting reaction at a processing temperature of 190°C and a screw speed of 200 rpm, with the material residence time controlled at approximately 3 minutes. After water cooling, pelletizing, and drying, maleic anhydride-grafted SEBS with a grafting rate of 1.2% is obtained.

[0081] The preparation method of epoxy-polydimethylsiloxane oligomers includes the following steps: Hydrogen-containing silicone oil and allyl glycidyl ether are weighed at a molar ratio of 1:1.2 (silicon-hydrogen bonds to carbon-carbon double bonds). The mixture is dehydrated at 110°C under vacuum for 2 hours. Subsequently, under nitrogen protection, the mixture is cooled to 90°C, and 50 ppm (by mass of the hydrogen-containing silicone oil) of Karstedt catalyst (platinum-vinylsiloxane complex) is added. The mixture is stirred at 90°C for 8 hours. After the reaction, epoxy-polydimethylsiloxane oligomers with an epoxy value of 0.15 are obtained.

[0082] The preparation method of nano-silica / hyperbranched polyester / ABS masterbatch includes the following steps: First, prepare hyperbranched polyester: trimethylolpropane and 2,2-dimethylolpropionic acid (DMPA) are mixed at a molar ratio of 1:30, and 3.0% by weight of p-toluenesulfonic acid catalyst is added. The mixture is then subjected to melt polycondensation at 160°C for 10 hours under nitrogen protection to obtain hydroxyl-terminated hyperbranched polyester. Second, nano-silica (particle size 20-50 nm) and the above-mentioned hyperbranched polyester are mixed at a mass ratio of 100:20 at 100°C for 30 minutes to ensure that the hyperbranched polyester fully coats the nano-silica, resulting in a pretreated composite powder. Finally, the pretreated composite powder and ABS resin are added to a twin-screw extruder at a mass ratio of 40:60, and the mixture is melt-blended, extruded, and granulated at a processing temperature of 220°C and a screw speed of 400 rpm to obtain nano-silica / hyperbranched polyester / ABS masterbatch.

[0083] The preparation method of N-alkyl-2,2,6,6-tetramethyl-4-aminopiperidine phosphonate includes the following steps: First, an N-alkylation reaction is carried out: (2,2,6,6-tetramethyl-piperidin-4-yl)-methylamine and iodoethane are weighed at a molar ratio of 1:1.5 and reacted at 110°C for 12 h in the presence of potassium carbonate to obtain an amine intermediate. Then, a phosphonylation reaction is carried out: the intermediate obtained in the previous step is weighed with dimethylphosphonochloride at a molar ratio of 1:1.2 and reacted at room temperature for 3 h in the presence of 1.5 molar amounts of triethylamine as an acid-binding agent to obtain a crude product reaction solution. Finally, the reaction solution is washed, separated, dried, concentrated, and purified by column chromatography to obtain the target product, N-ethyl-2,2,6,6-tetramethyl-4-aminopiperidine dimethylphosphonate.

[0084] Based on the raw material composition of the ABS composite material described above, this embodiment also provides a method for preparing the ABS composite material, including the following steps: S1. Weigh the ABS resin, maleic anhydride-grafted SEBS, nano masterbatch, N-alkyl-2,2,6,6-tetramethyl-4-aminopiperidine phosphonate and processing aids according to the formula and place them in a high-speed mixer. Mix at room temperature for 15 minutes to obtain a premix.

[0085] S2. The obtained premix is ​​added through the main feed port of the twin-screw extruder, while chopped carbon fibers are added through the side feed port. Epoxy-polydimethylsiloxane oligomer is injected through the liquid injection port located at the end of the melt section. The processing temperature of the twin-screw extruder is set to 220°C, and the screw speed to 400 rpm. Melt blending, reaction, and extrusion are carried out. The extruded strips are water-cooled, pelletized, and dried at 80°C for 4 hours to obtain the ABS composite material particles for mobile phone brackets in this embodiment.

[0086] Comparative Example 1 This comparative example is based on the disclosure in Example 2, with the following modifications: The raw material composition of ABS composite materials does not contain maleic anhydride-grafted hydrogenated styrene-butadiene-styrene block copolymer.

[0087] Comparative Example 2 This comparative example is based on the disclosure in Example 2, with the following modifications: In the raw material composition of ABS composite materials, maleic anhydride-grafted hydrogenated styrene-butadiene-styrene block copolymer is replaced with an equal mass of ordinary hydrogenated styrene-butadiene-styrene block copolymer.

[0088] Comparative Example 3 This comparative example is based on the disclosure in Example 2, with the following modifications: The raw material composition of ABS composite materials does not contain epoxy-dimethylsiloxane oligomers.

[0089] Comparative Example 4 This comparative example is based on the disclosure in Example 2, with the following modifications: The raw material composition of ABS composite materials does not contain short-cut carbon fibers.

[0090] Comparative Example 5 This comparative example is based on the disclosure in Example 2, with the following modifications: The raw material composition of ABS composite materials does not contain nano-silica / hyperbranched polyester / ABS masterbatch.

[0091] Comparative Example 6 This comparative example is based on the disclosure in Example 2, with the following modifications: The nano-silica / hyperbranched polyester / ABS masterbatch in the raw material composition of ABS composite material is replaced with an equal mass of ordinary nano-silica powder.

[0092] Comparative Example 7 This comparative example is based on the disclosure in Example 2, with the following modifications: The raw material composition of ABS composite materials does not contain N-alkyl-2,2,6,6-tetramethyl-4-aminopiperidine phosphonate.

[0093] To verify the comprehensive performance of the ABS composite material provided in this application, the material particles obtained in Examples 1-3 and Comparative Examples 1-7 were injection molded to prepare standard test strips, and the performance was measured according to the following national standard methods. The results are shown in Table 1.

[0094] The performance testing methods are as follows: Rigidity: According to the standard GB / T9341-2008 "Determination of Flexural Properties of Plastics", the flexural strength (MPa) and flexural modulus (MPa) are measured. The higher the value, the stronger the material rigidity.

[0095] Toughness: The notched impact strength (kJ / m²) was determined according to the standard GB / T1843-2008 "Determination of Impact Strength of Plastic Cantilever Beams". 2 The higher the value, the better the material's impact resistance and toughness.

[0096] Abrasion resistance: Tested according to GB / T3960-2016 "Plastics Sliding Friction and Wear Test Method" under specific loads and speeds, and expressed as wear loss (mg). The lower the value, the better the abrasion resistance of the material.

[0097] Anti-slip properties: The static coefficient of friction is measured in the same friction and wear test. A coefficient that remains within a moderate range (0.2–0.4) indicates that the material has both anti-slip and smooth feel.

[0098] Long-term stability: Heat resistance: The heat distortion temperature (HDT, ℃, 1.82MPa) was measured according to the standard GB / T1634.2-2019 "Determination of Deflection Temperature of Plastics under Load - Part 2". The higher the value, the better the dimensional stability of the material under heat.

[0099] Aging resistance: Xenon lamp aging test was conducted according to the standard GB / T16422.2-2014 Plastics Laboratory Light Source Exposure Test Method Part 2: Xenon Arc Lamp (total irradiance approximately 1500 MJ / m²). 2 The aging resistance of a material is characterized by the retention rate (%) of its notched impact strength before and after aging. The higher the retention rate, the better the long-term stability.

[0100] Table 1. Performance of ABS composite materials in the examples and comparative examples

[0101] As shown in Table 1, the three embodiments (Examples 1 to 3) provided in this application all exhibit a high performance range that is significantly better than that of ordinary ABS (see comparative baseline data) and is internally balanced in all key performance aspects.

[0102] In terms of rigidity, the flexural strength of the embodiment is between 102.3 and 125.8 MPa, and the flexural modulus is between 5800 and 8200 MPa, which represents a significant improvement compared to ordinary ABS (flexural strength of about 68.5 MPa and modulus of about 2300 MPa). This is mainly due to the reinforcement of the carbon fiber main skeleton and the secondary reinforcement of nano-silica.

[0103] In terms of toughness, the notched impact strength of the embodiments remained between 25.1 and 28.4 kJ / m.2 The high level of rigidity successfully maintained excellent impact resistance, which confirms that the functionalized toughening agent (SEBS-g-MAH) effectively improved the interface and achieved a balance between rigidity and toughness.

[0104] In terms of surface properties, the wear amount of the embodiments is as low as 6.9 to 9.2 mg, and the static friction coefficient is in the ideal range of 0.22 to 0.28, indicating that the material has both excellent wear resistance and moderate anti-slip feel, which is attributed to the chemical bonding and functionalization of reactive organosilicon on the surface.

[0105] Regarding long-term stability, the heat distortion temperature of the examples ranges from 98.5 to 104.7°C, indicating a significantly enhanced resistance to deformation at high temperatures. After aging tests, the impact strength retention rate is as high as 88.5% to 93.5%, demonstrating the material's excellent anti-aging properties. Among them, Example 2 exhibits the most balanced data and the best overall performance.

[0106] Comparative Example 1 (without SEBS-g-MAH): Its flexural strength and modulus (121.5 MPa, 7400 MPa) are comparable to those of Example 2, but its notched impact strength (15.2 kJ / m) is lower. 2 The toughness dropped sharply by about 47%. This directly proves that although the rigid reinforcing network is retained after the absence of maleic anhydride-grafted SEBS, the interfacial bond between the toughened rubber phase and the rigid ABS matrix is ​​weak, which cannot effectively transfer and dissipate impact energy, leading to material embrittlement. This highlights the irreplaceable role of SEBS-g-MAH as an "interfacial compatibilizer" in achieving high toughness.

[0107] Comparative Example 2 (using ordinary SEBS): Its performance was significantly lower than that of Example 2 across the board. This indicates that ordinary SEBS without maleic anhydride functionalization has poor compatibility with the ABS matrix, and its "physical blending" cannot achieve strong interfacial bonding, resulting in a lower toughening effect (19.8 kJ / m). 2 The effect is far inferior to that of chemically bonded SEBS-g-MAH, and it also slightly affects the dispersion and efficiency of other components, proving the key role of functionalization reaction in realizing the toughening potential of elastomers.

[0108] Comparative Example 3 (epoxy-free silicone): Its rigidity, toughness, and heat distortion temperature were similar to those of Example 2, but its surface properties were severely deteriorated: the wear loss (14.1 mg) surged by approximately 88%, and the static coefficient of friction (0.43) increased significantly. This clearly demonstrates that without the reactive silicone component, the material loses the in-situ formed surface wear-resistant and anti-slip functional layer, and its surface characteristics revert to a state close to that of pure ABS, characterized by easy wear and poor feel, proving the decisive contribution of this component to achieving durable surface functions.

[0109] Comparative Example 4 (without carbon fiber): Its stiffness indicators are severely insufficient: flexural strength (71.2 MPa) and flexural modulus (2550 MPa) both plummet to levels close to those of pure ABS, although its impact strength (29.8 kJ / m) is relatively high. 2 The highest value is achieved by chopped carbon fiber. This directly proves that chopped carbon fiber is the primary load-bearing skeleton providing macroscopic rigidity and strength. Without it, the overall rigid framework of the material cannot be established, and even with the presence of other toughening and nano-reinforcing components, the core requirement of high rigidity for the scaffold cannot be met.

[0110] Comparative Example 5 (without nano-masterbatch) and Comparative Example 6 (using ordinary nano-SiO2): The performance of both was significantly lower than that of Example 2, especially in terms of wear resistance (wear loss of 12.5 and 11.3 mg, respectively) and rigidity. The performance of Comparative Example 6 was better than that of Comparative Example 5, but both were inferior to that of Example 2. This collectively demonstrates that: First, the addition of nano-silica makes a clear contribution to improving rigidity, hardness, and wear resistance; Second, ordinary nanoparticles without hyperbranched polyester pretreatment (Comparative Example 6) are prone to agglomeration and have poor dispersion, limiting their full performance; Third, the complete absence of this component (Comparative Example 5) resulted in the greatest loss. This highlights the crucial technological value of "hyperbranched polyester pretreatment" in achieving efficient and stable dispersion of nanoparticles, thereby fully realizing their reinforcing, stiffening, and wear-resistant effects.

[0111] Comparative Example 7 (without phosphorus and nitrogen stabilizers): Its initial rigidity, toughness, and surface properties were very similar to those of Example 2, but its impact strength retention rate after long-term aging (72.5%) was much lower than that of Example 2 (92.1%). This comparison is crucial, demonstrating that the self-made phosphorus and nitrogen synergistic stabilizer is not effective in material processing and short-term use, but its intramolecular synergistic stabilization mechanism plays a unique and indispensable role in resisting long-term thermo-oxidative aging and preventing material performance degradation. Without it, the long-term durability of the material will be significantly reduced.

[0112] The range descriptions used herein, such as numerical ranges and proportional ranges, include all possible sub-ranges and single numerical values ​​within that range. For example, the range descriptions of "1 to 6" or "1 to 6" cover all sub-ranges (such as 1 to 3, 2 to 5, etc.) and single numbers (such as 1, 2, 3, 4, 5, 6) between 1 and 6. Unless otherwise specified, the terms "including" or "comprise" as used herein mean "including but not limited to". The proportional relationships mentioned herein, such as mass ratios and molar ratios, should be understood as the correspondence between the first and second terms of a proportional formula, according to the order of description. The raw materials, reagents, instruments, and equipment used herein can all be obtained commercially or prepared using existing methods.

[0113] The above description is merely a specific embodiment of this application, enabling those skilled in the art to understand or implement this application. Various modifications to these embodiments will be readily apparent to those skilled in the art. Therefore, this application is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features claimed herein.

Claims

1. An ABS composite material for a mobile phone holder, characterized in that, The ABS composite material, by weight, is composed of the following raw materials: ABS resin: 100 parts, maleic anhydride-grafted hydrogenated styrene-butadiene-styrene block copolymer: 8-15 parts, epoxy-polydimethylsiloxane oligomer: 2-5 parts, chopped carbon fiber: 5-10 parts, nano-silica / hyperbranched polyester / ABS masterbatch: 2-6 parts, N-alkyl-2,2,6,6-tetramethyl-4-aminopiperidine phosphonate: 0.3-1.0 parts, and processing aids: 0.5-1.5 parts; The preparation method of the nano-silica / hyperbranched polyester / ABS masterbatch includes the following steps: S301. Under nitrogen protection, trimethylolpropane, 2,2-dimethylolpropionic acid and p-toluenesulfonic acid catalyst are subjected to melt polycondensation reaction at 140-160°C for 6-10 hours to obtain hydroxyl-terminated hyperbranched polyester. S302. Mix nano-silica with the hyperbranched polyester at 80-100°C for 10-30 minutes to coat the surface of the nano-silica with the hyperbranched polyester, thereby obtaining a pretreated composite powder. S303. The pretreated composite powder and ABS resin are added to a twin-screw extruder for melt blending and extrusion granulation to obtain the nano-silica / hyperbranched polyester / ABS masterbatch. The processing temperature of the twin-screw extruder is 180–220°C, and the screw speed is 200–400 rpm. The preparation method of the epoxy-polydimethylsiloxane oligomer includes the following steps: S201. Under vacuum conditions of 90-110℃, hydrogen-containing silicone oil and allyl glycidyl ether are dehydrated for 1-2 hours to obtain a mixture. S202. Under inert gas protection, the mixture is cooled to 80-90°C, then Karstedt catalyst is added, and the mixture is stirred at 80-90°C for 4-8 hours to obtain the epoxy-polydimethylsiloxane oligomer.

2. The ABS composite material for a mobile phone holder according to claim 1, characterized in that, The preparation method of the maleic anhydride-grafted hydrogenated styrene-butadiene-styrene block copolymer includes the following steps: S101. Hydrogenated styrene-butadiene-styrene block copolymer, maleic anhydride monomer and dicumyl peroxide are stirred and mixed in a high-speed mixer at 60-80°C for 5-15 minutes to obtain a premix. S102. The premixed material is fed into a twin-screw extruder and subjected to a grafting reaction under melting temperature and shearing action. After water cooling and pelletizing, the maleic anhydride-grafted hydrogenated styrene-butadiene-styrene block copolymer is obtained. The mass ratio of the hydrogenated styrene-butadiene-styrene block copolymer, the maleic anhydride monomer, and the dicumyl peroxide is 100:(0.8-2.0):(0.1-0.4). The twin-screw extruder has a processing temperature of 170–190℃, a screw speed of 80–200 rpm, and a material residence time of 1–3 min. The grafting rate of the maleic anhydride-grafted hydrogenated styrene-butadiene-styrene block copolymer is 0.8-1.2%.

3. The ABS composite material for a mobile phone holder according to claim 1, characterized in that, The molar ratio of the silicon-hydrogen bonds in the hydrogen-containing silicone oil to the carbon-carbon double bonds in the allyl glycidyl ether is 1:(1.0-1.2). The mass of the Karstedt catalyst is 5 to 50 ppm of the mass of the hydrogen-containing silicone oil; The epoxy value of the epoxy-polydimethylsiloxane oligomer is 0.05 to 0.

15.

4. The ABS composite material for a mobile phone holder according to claim 1, characterized in that, The molar ratio of trimethylolpropane to 2,2-dimethylolpropionic acid is 1:(15-30); The mass of the p-toluenesulfonic acid catalyst is 1.0 to 3.0% of the mass of the 2,2-dimethylolpropionic acid. The mass ratio of the nano-silica to the hyperbranched polyester is 100:(5-20); The mass ratio of the pretreated composite powder to the ABS resin is (20-40):(60-80).

5. The ABS composite material for a mobile phone holder according to claim 1, characterized in that, The method for preparing the N-alkyl-2,2,6,6-tetramethyl-4-aminopiperidine phosphonate includes the following steps: S401. In the presence of potassium carbonate, (2,2,6,6-tetramethyl-piperidin-4-yl)-methylamine is reacted with iodoethane at 60-110 °C for 4-12 h to obtain an intermediate; S402. In the presence of the acid-binding agent triethylamine, the intermediate is subjected to a phosphonylation reaction with dimethylphosphonic chloride at room temperature for 1-3 hours to obtain a reaction solution containing the crude product. S403. The reaction solution is washed, separated, dried and concentrated, and then purified to obtain the N-alkyl-2,2,6,6-tetramethyl-4-aminopiperidine phosphonate.

6. The ABS composite material for a mobile phone holder according to claim 5, characterized in that, The molar ratio of (2,2,6,6-tetramethyl-piperidin-4-yl)-methylamine to iodoethane is 1:(1.0-1.5); The molar ratio of the intermediate to the dimethylphosphonic chloride is 1:(1.0-1.2), and the molar ratio of the triethylamine to the dimethylphosphonic chloride is (1.0-1.5):

1.

7. The ABS composite material for a mobile phone holder according to claim 1, characterized in that, The processing aid is composed of a primary antioxidant, an auxiliary antioxidant, and an internal lubricant, wherein the mass ratio of the primary antioxidant, the auxiliary antioxidant, and the internal lubricant is (1-5):(2-8):(2-8); The primary antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]; The auxiliary antioxidant is tris(2,4-di-tert-butylphenyl) phosphite; The internal lubricant is N,N'-ethylene bis-stearamide.

8. The ABS composite material for a mobile phone holder according to claim 1, characterized in that, The chopped carbon fibers have a length of 3–6 mm and a diameter of 5–9 μm.

9. A method for preparing an ABS composite material for a mobile phone holder according to any one of claims 1 to 8, characterized in that, The method includes the following steps: S1. Place ABS resin, maleic anhydride-grafted hydrogenated styrene-butadiene-styrene block copolymer, nano silica / hyperbranched polyester / ABS masterbatch, N-alkyl-2,2,6,6-tetramethyl-4-aminopiperidine phosphonate and processing aids in a high-speed mixer and mix at room temperature for 5-15 minutes to obtain a premix. S2. The premixed material is added from the main feed port of the twin-screw extruder, short-cut carbon fibers are added from the side feed port, and epoxy-polydimethylsiloxane oligomer is injected through the liquid injection port located at the end of the melting section. The mixture is melt-blended, reacted and extruded at a processing temperature of 180-220°C and a screw speed of 200-400 rpm. After water cooling, pelletizing and drying, the ABS composite material is obtained.

Citation Information

Patent Citations

  • Machine for painting wheels

    CA104154A

  • Heat resistance ABS material and preparation method thereof

    CN103087456A

  • Low-dielectric-constant polyphenylene sulfide composition and preparation method thereof

    CN111334042A